2020
DOI: 10.1371/journal.pone.0244585
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing practices of dentists for endodontic infections; a cross-sectional study

Abstract: Objective The indiscriminate prescription of antibiotics has led to the emergence of resistance microbes worldwide. This study aimed to investigate the antibiotic prescribing practices amongst general dental practitioners and specialists in managing endodontic infections in the United Arab Emirates (UAE). Design General dental practitioners and specialists in the UAE were invited to participate in an online questionnaire survey which included questions on socio-demographics, practitioner’s antibiotic prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…Many of the findings of the study confirm findings from previous studies conducted across India, Malaysia, and Saudi Arabia that reported an excess use of antibiotics in situations where they may not be required [17,18]. Our study found that broad-spectrum antibiotics especially were being overprescribed in situations where they were not required such as irreversible pulpitis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Many of the findings of the study confirm findings from previous studies conducted across India, Malaysia, and Saudi Arabia that reported an excess use of antibiotics in situations where they may not be required [17,18]. Our study found that broad-spectrum antibiotics especially were being overprescribed in situations where they were not required such as irreversible pulpitis.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, there have been studies conducted in developing countries such as India, Saudi Arabia, and Malaysia where it has been shown that the antibiotic prescribing practices were exceedingly flawed [17][18][19][20]. These studies also concluded with the obvious need for educational programs and initiatives that could help rationalize the use of antibiotics by dental practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been an increase in the prescribing of antibiotics for patients with suspected or confirmed COVID-19 in Bangladesh, similar to other countries, despite only a limited number of patients with COVID-19 having confirmed bacterial or fungal infections [12][13][14][15] . This builds on existing high and inappropriate rates of prescribing and dispensing of antibiotics generally in Bangladesh and wider among low-and middle-income countries (LMICs) including among dentists [16][17][18][19][20] . This is a concern as the over-use of antimicrobials increases antimicrobial resistance (AMR) with subsequent implications on morbidity, mortality and costs [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…The American Association of Endodontics (AAE) and the European Society of Endodontology (ESE) frequently revise the guidelines for endodontists regarding proper antibiotic prescription. There is general consensus that in most clinical endodontic situations, it suffices to provide local treatment with removal or reduction of the infection source, without using systemic antibiotics [8][9][10] . Different studies around the world have shown that dentists still prescribe antibiotics unnecessarily in endodontics [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%